Determinants of women’s wage differential compensation sensitivity and residential sectorial diversity of it: An exploratory study in Sri Lanka - Wijayawardhana, W.M.P.M.; Siriwardhane, D.R.J. (My University, 2022)
Purpose- This study explores the determinants of women's wage differential compensation sensitivity (WWCS) in terms of female labor force participation and examines the nature of residential sectorial (urban, rural, and estate) diversity of this sensitivity in Sri Lanka. Design/methodology/approach – This exploratory study involved a qualitative indepth analysis of the evidence of wage differential compensation sensitivity through an empirical study in Sri Lanka. The data collection for this study was done through an interview procedure and it has adopted a snowballing sampling technique to select subjects for the sample. In line with this approach, the researcher has recruited sample members from three separate clusters namely urban, rural, and estate residential sectorial clusters. Qualitative data was analyzed through the reflexive thematic analysis approach which was introduced by Braun and Clarke. Findings – This study found that rural females are highly sensitive to wage differential compensation in terms of labor force participation and estate females showed the least sensitivity. Motherhood and child age, co-habitation of grandparents, male supremacy in traditionally patriarchal families, intergenerational education & learning, voluntary child labor, human trafficking for women labor exploitation, and growth needs & domestic financial requirements are recognized as the determinants of women‟s wage differential compensation sensitivity.
Keywords: Female labor force participation, Thematic Analysis, Sri Lanka, Women’s wage differential compensation